2007
DOI: 10.1002/jgt.20270
|View full text |Cite
|
Sign up to set email alerts
|

Graph classes characterized both by forbidden subgraphs and degree sequences

Abstract: Given a set F of graphs, a graph G is F-free if G does not contain any member of F as an induced subgraph. We say that F is a degree-sequence-forcing set if, for each graph G in the class C of F-free graphs, every realization of the degree sequence of G is also in C. We give a complete characterization of the degree-sequence-forcing sets F when F has cardinality at most two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Let G be a degree-sequence-forcing set. By Propositions 28, 29 and 31, and Corollary 30, we have that either min{|V 1 …”
Section: Proof For Any Bipartitioned Graphmentioning
confidence: 88%
See 4 more Smart Citations
“…Let G be a degree-sequence-forcing set. By Propositions 28, 29 and 31, and Corollary 30, we have that either min{|V 1 …”
Section: Proof For Any Bipartitioned Graphmentioning
confidence: 88%
“…The authors showed in [1] that any graph that forbids any of the degree-sequence-forcing singletons or pairs other than {2K 2 , C 4 } is a unigraph. Thus any graph that forbids one of these sets and also forbids an additional graph is a unigraph.…”
Section: Propositionmentioning
confidence: 99%
See 3 more Smart Citations